A multicenter phase II trial evaluating the efficacy of bevacizumab plus mFOLFOX6 for R0 surgical resection in advanced colorectal liver metastases harboring mutant-type KRAS: NEXTO-mt trial. Issue 8 (August 2022) - Watanabe, Genki; Mise, Yoshihiro; Oba, Masaru; Saiura, Akio; Inoue, Yosuke; Takahashi, Yu; Kishi, Yoji; Suyama, Koichi; Takayama, Tadatoshi; Noie, Tamaki; Nishioka, Yujiro; Akamatsu, Nobuhisa; et al.
Abstract: Background: The effect of bevacizumab plus mFOLFOX6 on downsizing of liver metastases for curative resection has not been well assessed for patients with advanced colorectal liver metastases (CRLMs). This multicenter phase II trial aimed to examine the efficacy and safety of bevacizumab plus mFOLFOX6 for advanced CRLMs harboring mutant-type KRAS. Methods: Patients with advanced CRLMs (tumor number of ≥5 and/or technically unresectable) harboring mutant-type KRAS were included. Surgical indication was evaluated every 4 cycles of bevacizumab plus mFOLFOX6. Liver resection was planned if the CRLMs were resectable. The primary endpoint was R0 resection rate. The secondary endpoints included overall survival (OS), recurrence-free survival, progression-free survival, and safety. Results: Between 2013 and 2017, 29 patients from six centers were registered. The rates of complete and partial responses were 0% and 62.1%, respectively. R0 and R1 resections were performed in 19 and 1 patient, respectively (R0 resection rate: 65.5%). No mortality occurred. During the median follow-up of 30.7 months, the 3-year OS rate for all the patients was 64.4% with the median survival of 49.1 months. Conclusion: For advanced CRLMs harboring mutant-type KRAS, bevacizumab plus mFOLFOX6 achieved a high R0 resection rate, leading to favorable survival.